The role of epitaxial strain on photoconductive performance in LaNiO3 epitaxial thin films. Issue 12 (15th June 2023) - Li, Jie; Liu, Haifeng; Wu, Hongwei; Yang, Jiacheng; Deng, Ting; Liu, Sili; Xie, Ruishi; Guo, Baogang; Zhang, Xingquan; Zheng, Kui; Huo, Jichuan
Abstract: In this work, LaNiO3 epitaxial thin films on (001) single-crystal LaAlO3 and SrTiO3 substrates were deposited by polymer assisted deposition method, respectively. Additionally, LaNiO3 polycrystalline film was coated on ceramic substrate using LaNiO3 powder obtained from precursor solution in polymer assisted deposition. Due to the difference of lattice mismatch between LaNiO3 and single-crystal substrates, LaNiO3 thin films suffer different epitaxial strain, resulting in distortion of NiO6 octahedrons which increases with the intensity of strain. Such phenomena lead to the decrease of the field splitting energy of NiO6 octahedron and the band gap value of LaNiO3, further increasing the charge transition and enhancing the visible-light photoconductivity. The existence of epitaxial strain brings more Ni 2+ and adsorbed oxygen into perovskite type LaNiO3, introduces more oxygen vacancy defects, reduces the complex rate of photo induced electron-hole pairs, and thereby improves the photoelectric activity of LaNiO3 . This work provides a feasible method to control the structure distortion and photoconductivity effect of all-inorganic perovskite. Graphical abstract: Image 1